MHD Casson Nanofluid Past a Stretching Sheet with the Effects of Viscous Dissipation, Chemical Reaction and Heat Source/Sink - G. Narender; K. Govardhan; G. Sreedhar Sarma (Journal of Applied and Computational Mechanics, 2021)
The effects of viscous dissipation, chemical reaction and activation energy on the two-dimensional hydromagnetic convective heat and mass transfer flow of a Casson nanofluid fluid over a stretching sheet with thermal radiation, have been discussed in detail. The formulated highly nonlinear equations for the above-mentioned flow are converted into first-order ordinary differential equations (ODEs). The shooting method along with Adams-Bash forth Moulton method is used to solve the BVP by using the Fortran language program. The numerical results are computed by choosing different values of the involved physical parameters and compared with earlier published results and excellent validation of the present numerical results has been achieved for local Nusselt number and local Sherwood number. The graphical numerical results of different physical quantities of interest are presented to analyze their dynamics under the varying physical quantities. From the results, it has been remarked that the heat transfer rate escalates for the large values of radiation parameter, viscous dissipation for the Casson nanofluid.